Optic neuritis in various demyelinating diseases - Kalashnikova, A. K.; Eliseeva, D. D.; Andreeva, N. A.; Zhorzholadze, N. V.; Ronzina, I. A.; Bembeeva, R. Ts; Venediktova, N. N.; Kalganova, M. R.; Sheremet, N. L. (Nevrologii͡a︡, neĭropsikhiatrii͡a︡, psikhosomatika, 2024)
The discovery of antibodies against aquaporin-4 (AQP4) and against myelinoligodendrocyte glycoprotein (MOG) confirmed the existence of two disease entities distinct from multiple sclerosis (MS) — neuromyelitis optica spectrum disorders (NMOSD) and myelinoligodendrocyte glycoprotein-associated disease (MOGAD). Demyelinating optic neuritis (ON) can be either idiopathic (iDON) or a manifestation of MS, NMOSD (AQP4-ON) or MOGAD (MOG-ON). Objective : to determine the clinical features of ON and to evaluate the diagnostic value of optical coherence tomography (OCT) in demyelinating diseases of the central nervous system. Material and methods . The study included 43 patients with demyelinating ON who were divided into three groups according to the underlying disease (NMOSD, MOGAD and MS/iDON). We assessed visual acuity (VA) in the acute phase and analyzed VA and average values of retinal nerve fiber layer thickness (RNFL) and retinal ganglion cell complex (RGC) thickness using OCT data 6 months after the onset of ON. Results . ON was observed in the onset of the disease in 75% of NMOSD patients, 62% of MOGAD patients and 86% of MS/iDON patients. In the MOGAD and NMOSD groups, bilateral ON was predominantly observed. In 65% of patients with MOGAD (MOG-ONr), a recurrent course of ON was observed. VA was significantly lower in patients with AQP4-ON in acute phase and comparable to the MOG-ONr group in the long-term phase. VA in the onset of MOG-ON with a single episode was comparable to that of MS/iDON (p=0.2), but recovery was less pronounced (p=0.03). The most significant thinning of the RNFL and RGC complex was observed in the AQP4-ON and MOG-ONr groups. In AQP4-ON and MOG-ON groups, restoration of VA up to 0.5 and higher was observed significantly more frequently in the group of patients receiving pulse therapy with glucocorticoids (p=0.018). Conclusion . The study showed the most pronounced structural and functional disturbances in the long-term phase of AQP4-ON and MOG-ONr. MOG-ON was characterized by a high frequency of relapses with the influence of this factor on VA and thinning of the retinal layers in the long-term.